2023
DOI: 10.33050/sensi.v9i1.2623
|View full text |Cite
|
Sign up to set email alerts
|

Rancang Bangun Sistem Pemilahan dan Pengangkutan Sampah Wilayah Provinsi DKI Jakarta Berbasis Website Dengan Metode Prototype

Abstract: Data pemilahan dan pengangkutan sampah terjadwal pada Dinas Lingkungan Hidup Provinsi DKI Jakarta masih menggunakan buku catatan/manual dan menggunakan Google From. Hal ini mempersulit bagi pimpinan/kepala Dinas Lingkungan Hidup Provinsi DKIJakarta untuk memonitoring seluruh data laporan pemilahan dan pengangkutan sampah terjadwal di wilayah DKI Jakarta. Penelitian ini  mengembangkan sebuah aplikasi dari permasalahan tersebutyakni pemilahan dan pengangkutan sampah terjadwal berbasis web sehingga meringankan Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Subsequently, respondents were asked to provide feedback, and it was found that the three most desired features by respondents were the scheduled waste collection service feature that can be customized to their demand, with 87 percent. Rahman and Setiawati (2023) found that the analysis of the information system for inputting, sorting, and collecting waste at the Jakarta Provincial Environmental Service is still simple, using paper media as input tools and computers Figure 6. "Reclapan" Prototype Solution testing shows that 89.9 percent of respondents find using "Reclapan" more practical compared to their current waste management methods.…”
Section: Solution Testingmentioning
confidence: 99%
“…Subsequently, respondents were asked to provide feedback, and it was found that the three most desired features by respondents were the scheduled waste collection service feature that can be customized to their demand, with 87 percent. Rahman and Setiawati (2023) found that the analysis of the information system for inputting, sorting, and collecting waste at the Jakarta Provincial Environmental Service is still simple, using paper media as input tools and computers Figure 6. "Reclapan" Prototype Solution testing shows that 89.9 percent of respondents find using "Reclapan" more practical compared to their current waste management methods.…”
Section: Solution Testingmentioning
confidence: 99%
“…Dalam konteks pengelolaan pengangkutan sampah, telah dilakukan penelitian dalam rancang bangun sistem pemilahan dan pengangkutan sampah wilayah Provinsi DKI Jakarta berbasis website dengan metode prototype. Sistem ini memiliki output yang dapat memudahkan petugas TPS dalam penginputan data, pengawas TPS dalam melakukan monitoring data sampah, pengawas Dinas dalam memvalidasi dan merekapitulasi data, serta pimpinan dalam mengambil hasil rekapan laporan data sampah [5].…”
Section: Pendahuluanunclassified